2016
DOI: 10.1371/journal.pone.0153462
|View full text |Cite
|
Sign up to set email alerts
|

Diminished COX-2/PGE2-Mediated Antiviral Response Due to Impaired NOX/MAPK Signaling in G6PD-Knockdown Lung Epithelial Cells

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) provides the reducing agent NADPH to meet the cellular needs for reductive biosynthesis and the maintenance of redox homeostasis. G6PD-deficient cells experience a high level of oxidative stress and an increased susceptibility to viral infections. Cyclooxygenase-2 (COX-2) is a key mediator in the regulation of viral replication and inflammatory response. In the current study, the role of G6PD on the inflammatory response was determined in both scramble control and G6PD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 54 publications
(67 reference statements)
2
23
0
Order By: Relevance
“…The results from the present study and from previous studies suggested that G6PD may promote ROS production in RCC cells (16,49). Previous studies also reported a possible interaction between G6PD expression and the MAPK signaling pathway (59,60).…”
Section: Discussionsupporting
confidence: 80%
“…The results from the present study and from previous studies suggested that G6PD may promote ROS production in RCC cells (16,49). Previous studies also reported a possible interaction between G6PD expression and the MAPK signaling pathway (59,60).…”
Section: Discussionsupporting
confidence: 80%
“…It has been reported that, G6PD plays important roles in the regulation of reactive oxygen species (ROS) generation [ 1 ]. As the PPP is activated, G6PD is usually considered the pacesetter for nicotinamide adenine dinucleotide phosphate (NADPH) production in cancer cells [ 1 , 2 , 13 ]. NADPH is a substrate of NADPH oxidases and functionally important hydrogen donor that serves as a cofactor in anabolic reactions of fatty acids, isoprenoids, and aromatic amino acids synthesis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…NOX4, especially the membrane-bound NOX4, plays a major role in regulating cellular functions and is thought to be an electron transporter [ 13 , 15 , 21 ]. In combination with NADPH, NOX4 could pass the electrons to an electron acceptor according to the equation NADPH→FAD→Heme→O 2 to generate O 2 -.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…G6PD modulates xenobiotic metabolism via the Nrf2 signaling pathway and affects the xenobiotic metabolizing enzyme expression 5 . Moreover, it acts as a key regulator of the cellular inflammatory and immune response against viral infection 6 , 7 . Because G6PD is a rate-limiting enzyme in the pentose-phosphate shunt, it is essential for regulating energy consumption and glucose metabolism 8 .…”
Section: Introductionmentioning
confidence: 99%